GESTIÓN Y FORTALECIMIENTO DE PROYECTOS COMUNITARIOS: UNA OPCIÓN PARA EL DESARROLLO TURÍSTICO SUSTENTABLE EN COMUNIDADES RURALES DEL ESTADO DE CHIHUAHUA(CASO EJIDO OJO DE LA CASA) - Chaparro, Rosa Herminia Suárez; Silva, Francisco Arturo Bribiescas; Villalpando, Jorge Villanueva (European Scientific Journal, ESJ, 2013)
"The Regional Development Model” of the state of Chihuahua in regards to the tourism activity is determined by an exogenous context, that is based on national and international models besides of being subject to national, state and local policies that generate a social exclusion, regional contrasts and polarization that result in antagonisms, economic instability, social inequality and damage to the environment in the rural communities. Due to the preceding argument this research paper is working on a proposal that presents the development of a sustainable alternative for the rural communities of the state of Chihuahua, Mexico, starting with the management and strengthening of the community projects focused in the nature and community tourism in the Common Land “Ojo de la Casa”, located in the municipal section of Samalayuca, Chihuahua, Mexico.